Laying foundations for successful customer relationship management - the case of landing jobs - Nunes, Maria João Teixeira (2020)
The purpose of this study is to lay the foundations forLanding.jobs tobuildsuccessful customer relationship strategies, dueto the need for automation in dealing with customersrecently created by the company’s expansion.After reviewing Customer Relationship Management (CRM) literature focused on success factors and challenges of implementing CRM strategies, a descriptive analysis of Landing.jobs’ user base was performed, as well as an in-depth review of its customer journey and assessment of pains, finalized with an online survey to gather talent insights. Overall, Landing.jobs needs focusing on gathering quality knowledge on talent, which was concluded to be eased by implementing a CRM software to manage more efficiently the relationship with the customer base.